KELAYAKAN FINANSIAL PENGGEMUKAN KAMBING POTONG DI KOTA SANGATTA - Nursida Nursida; Hadi Susanto (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2017)
This study aims to determine the income and financial feasibility of fettening goat business in Sangatta city.  The time of the study was conducted in February 2017 with case study at three locations of fattening business.  The determination of business location is done purposively at Rudina street, Pibang Dalam and Kabo street with the consideration that the fattening business has been going on for over five years.  The income analysis use TR, TR and π, while financial feasibility is analyzed by BEP, PP, NVP, B/C Ratio and IRR analysis.  The results showed that the average income of goat fattening business in the city of Sangatta from 2012 until 2016 amounted to Rp 304.063.933.  the BEP (price) and BEP (product) value of Rp. 1.707.107/head and 645 fish while the average selling price is Rp. 2.066.667/head and the average production amount of 743 heads.  The value of PP is 2.33≤ 5 years, NVP of 253,716,577≥0, B/C ratio of 1.78≥1, and IRR value of 31.95% ≥ 10,50%.  Based on the criteria, financial the goat fattening business in Sangatta city is feasible to be developed.